1999
DOI: 10.1093/molehr/5.11.1017
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human sperm capacitation by a cholesterol efflux-stimulated signal transduction pathway leading to protein kinase A-mediated up-regulation of protein tyrosine phosphorylation

Abstract: Protein tyrosine phosphorylation is an important intracellular event accompanying the in-vitro capacitation of mouse, bovine and human spermatozoa. Here, we demonstrate that bovine serum albumin (BSA) and NaHCO(3) are required for protein tyrosine phosphorylation in ejaculated human spermatozoa. The absence of protein tyrosine phosphorylation in media minus these two constituents could be recovered by addition to the media of cAMP analogues and/or phosphodiesterase inhibitors. Since BSA is postulated to modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
161
2
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(179 citation statements)
references
References 44 publications
11
161
2
5
Order By: Relevance
“…Levels of tyrosine phosphorylation were comparable to the ones observed in CM medium (Bedu-Addo et al 2005). These results support the use of sperm protein tyrosine phosphorylation as a marker of cells undergoing capacitation (Visconti et al 1995a, 1995b, Leclerc et al 1996, Osheroff et al 1999, but suggest that tyrosine phosphorylation is not a diagnostic marker of capacitated cells.…”
Section: Events Associated With Sperm Capacitationsupporting
confidence: 75%
See 2 more Smart Citations
“…Levels of tyrosine phosphorylation were comparable to the ones observed in CM medium (Bedu-Addo et al 2005). These results support the use of sperm protein tyrosine phosphorylation as a marker of cells undergoing capacitation (Visconti et al 1995a, 1995b, Leclerc et al 1996, Osheroff et al 1999, but suggest that tyrosine phosphorylation is not a diagnostic marker of capacitated cells.…”
Section: Events Associated With Sperm Capacitationsupporting
confidence: 75%
“…Tyrosine phosphorylation of sperm proteins is a wellestablished and widely-used marker for cells undergoing capacitation (Visconti et al 1995a, 1995b, Leclerc et al 1996, Osheroff et al 1999. In our recent experiments, we showed that when spermatozoa were incubated in CM for 6 h and then resuspended in CM without bicarbonate or CM without albumin for an additional hour, the cells lost their ability to undergo acrosome reaction (Bedu-Addo et al 2005).…”
Section: Events Associated With Sperm Capacitationmentioning
confidence: 71%
See 1 more Smart Citation
“…The proposed concept can also explain the inability of HSPA8 to enhance the viability of capacitated spermatozoa. Capacitation involves substantial reduction in membrane cholesterol (Osheroff et al 1999). It is therefore highly probable that the capacitation-induced reduction/reorganization in sperm membrane cholesterol/lipid structure compromises the interaction sites for HSPA8 to assert its effects.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been made to supplement the culture media with natural additives like serum (Kane and Headon, 1980;Totey et al 1993), follicular fluid (Calvo et al 1989), oviductal fluid I (Zhu et al 1994), human tubal fluid (Maeda et al 1996;Osheroff et al 1999), cumulus cells (Hartshorne, 1989;Xu et al 1992;Madan et al 1994;Watson et al 1994), granulosa cells (Motlik and Fulka, 1981;Vongpralub and Koyanagi, 1994), and oviductal cells (Minami et al 1994;Li et al 2001). However, the use of bovine amniotic fluid as a constituent of culture medium for in vitro maturation, IVF and embryonic development has not been reported, although, amniotic fluid contains different electrolytes, non-protein and protein components (Johnson and Everitt, 1988).…”
Section: Introductionmentioning
confidence: 99%